Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)

Recruiting doctors from and for underserved groups: Does New Brunswick's initiative to recruit doctors for its linguistic minority help rural communities? - Beauchamp, Jacinthe; Bélanger, Mathieu; Schofield, Aurel; Bordage, Rachel; Donovan, Denise; Landry, Michel (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objectives Within health care, there are underserved groups. New Brunswick’s French-speaking minority, which also mostly lives in rural communities, is one such group. A physician shortage potentially prevents this population from accessing health promotion and clinical prevention services. This study analyzes whether New Brunswick Francophone doctors with rural backgrounds are more likely than doctors from urban regions to set up practice in rural communities of the province. Methods A questionnaire was sent to 390 New Brunswick Francophone physicians admitted in medicine between 1973 and 2000. It collected information on geographic origin and history of medical practice. Multivariate logistic regressions were used to identify whether a rural background is associated with the likelihood of ever and currently practicing in rural communities. We used the General Practice Rurality Index-simplified to quantify the rurality level of communities. Results In total, 264 (67%) physicians participated. A rural background was positively associated with the establishment of a first medical practice in a rural community. This relationship was only significant among family physicians. There was no statistically significant relationship between rurality of community of origin and rurality of current community of practice among either family or specialty physicians. Conclusion Although Francophone doctors with a rural background were more likely than their urban counterparts to set up their first practice in a rural community, this effect was not sustained. This raises questions as to why they leave rural communities and highlights the importance of measures to retain doctors as a way to promote public health for underserved rural groups.

Accès au diagnostic précoce de démence au Nouveau-Brunswick : perceptions d’usagers potentiels de services selon la langue et le milieu de vie - Pakzad, Sarah; Jbilou, Jalila; Paulin, Marie-Claire; Fontaine, Véronique; Donovan, Denise; Bélanger, Mathieu; Bourque, Paul-Émile (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Le diagnostic précoce de la démence (DPD) est crucial autant pour l’identification des causes réversibles que pour la mise en place rapide d’interventions de prévention secondaire et de prise en charge thérapeutique. Cette étude explore la perception d’aînés du Nouveau-Brunswick concernant l’accessibilité, la disponibilité et la satisfaction des services de DPD, en tenant compte de leur langue d’usage et de leur milieu de vie (urbain ou rural). Méthode Questionnaire auto-administré explorant les perceptions d’aînés francophones et anglophones de régions rurales et urbaines du Nouveau-Brunswick concernant les services de DPD. Des analyses univariées et bivariées ont été réalisées. Résultats Parmi les 157 participants âgés de 65 ans et plus ayant répondu au questionnaire et dont les données ont été analysées, 84 déclarent être principalement francophones et 72 parmi eux vivent en milieu rural. Les analyses bivariées suggèrent que les groupes linguistiques étudiés sont comparables en ce qui concerne leurs perceptions de la disponibilité, l’accès et la satisfaction des services de DPD. Toutefois, l’introduction de la dimension géographique montre des disparités intragroupes et intergroupes linguistiques, notamment en ce qui a trait à l’information relative au type de services disponibles dans la région. Conclusion Ces résultats suggèrent que les aînés vivant en milieu rural au Nouveau-Brunswick représentent un groupe particulièrement vulnérable ayant une perception d’accès limité aux services de DPD dans leur région.

Perceived Health status of Francophones and Anglophones in an official bilingual Canadian province - Bélanger, Mathieu; Bouchard, Louise; Gaboury, Isabelle; Sonier, Brigitte; Gagnon-Arpin, Isabelle; Schofield, Aurel; Bourque, Paul-Emile (Canadian Journal of Public health, 2011)
Objective: It has been reported that being part of a minority group may be negatively associated with self-perceived health. The objective of this analysis was to determine whether there are differences in perceived health between the Francophone minority and Anglophone majority in New Brunswick, the only officially bilingual province in Canada. Methods: Data from the first four primary cycles of the Canadian Community Health Survey (2001 to 2007) were obtained for 17,729 New Brunswick residents. Odds of reporting good health among Francophones and Anglophones were compared using multivariate logistic regressions accounting for age, health-related behaviours, socio-demographic variables, and medical conditions. Results: In the final models, Francophone men and women were less likely than Anglophones to report their health as being good, although these differences were not statistically significant (Odds ratio, 95% confidence interval: 0.88, 0.61–1.26; 0.71, 0.49-1.04, in men and women, respectively). Conclusion: This study suggests that being part of the linguistic minority in New Brunswick is not associated with statistically significant differences in self-perceived health.

Étude exploratoire : perceptions, croyances, connaissances et attitudes d’un groupe d’aînés francophones du Nouveau-Brunswick concernant la démence et son diagnostic - Pakzad, Sarah; Paulin, Marie-Claire; Jbilou, Jalila; Fontaine, Véronique; Bourque, Paul-Émile; Bélanger, Mathieu; Routhier, Nicholas; Lavoie, Anne Marise (Reflets, 2012)
Cette étude explore les perceptions, croyances, connaissances et attitudes d’un groupe d’aînés francophones du Nouveau-Brunswick face à la démence et à son diagnostic; le diagnostic précoce de la démence est crucial autant pour l’identification des causes réversibles que pour la mise en place rapide d’interventions de prévention secondaire. Quatre-vingt-onze francophones du Nouveau-Brunswick âgés de 65 ans et plus ont été interrogés face à la démence et à son diagnostic dans cette étude quantitative exploratoire. Entre autres, bien que les participants de cette étude aient rapporté avoir peur de recevoir un diagnostic de démence, la plupart voudraient recevoir le diagnostic s’ils en étaient atteints. Les résultats soulignent l’importance d’éduquer la population face à la démence et aux services d’évaluation de la démence. D’autres implications sont discutées. Mots-clés : Démence, diagnostic, intention, maladie d’Alzheimer, minorité linguistique